Anatomical profile and genetic variability of sweet potato (Ipomoea batatas) cultivars in Banyumas, Central Java, based on RAPD markers - SITI SAMIYARSIH; nur fitrianto; ENUR AZIZAH; WIWIK HERAWATI; ROCHMATINO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Samiyarsih S, Fitrianto N, Azizah E, Herawati W, Rochmatino. 2020. Anatomical profile and genetic variability of sweet potato (Ipomoea batatas) cultivars in Banyumas, Central Java, based on RAPD markers. Biodiversitas 21: 1755-1766. Indonesia has developed a food consumption diversification based on local sources. Sweet potato (Ipomoea batatas) is one of the tubers of carbohydrate sources in addition to wheat, rice, corn, potatoes, and cassava. It has a wide distribution, and high cultivars diversity produces a high variation on its morphology, anatomy, and genetic modification. The objectives of this research were to investigate the anatomical profile and genetic variability of eight sweet potatoes (Ipomoea batatas) cultivars found in Banyumas, Central Java, Indonesia. Anatomical profile was observed by the embedding method and subjected to analysis of variance. DNA amplification using Random Amplified Polymorphic DNA (RAPD) method with 10 primers, namely OPA-1, OPA-2, OPA-3, OPA-4, OPA-9, OPA-11, OPA-13, OPA-15, OPA-16, and OPA-18. The result of the anatomical study showed that eight sweet potato cultivars have significantly different (p<0.05) variation in leaf anatomical profile. RAPD primers produced 52 amplified fragments varying from 100 to 1300 bp in size, and 90.40% of the amplification bands were polymorphic. The genetic similarity level is ranged from 0.37 to 0.93. Two unspecific groups were forming at a coefficient of 55% from the dendrogram. The first group consisted of one cultivar, Cangkuang, and the second group consisted of seven cultivars Antin, Ungu Tua, Borobudur, Sukuh, Sari, Beta, and Kidal. The nearest relationships cultivars were Borobudur, and Ungu Tua had the highest similarity coefficient of 93%, and the lowest similarity found in Cangkuang and Antin with a coefficient of 37%. The range of genetic distance of eight cultivars was from 0.37-0.93. Implementation of the research would particularly useful for the identification and evaluation of the genetic improvement of sweet potato cultivars.